INSCYD physiological performance software is valid to determine the maximal lactate steady state in male and female cyclists - Poffé, Chiel; Van Dael, Kaat; Van Schuylenbergh, Reinout (Frontiers in Sports and Active Living, 2024)
The maximal lactate steady state (MLSS) is defined as the highest workload that can be maintained without blood lactate accumulation over time. The power output at MLSS (PMLSS) is regularly implemented to define training zones, to quantify training progress, or to predict race performance. Gold standard methodology for MLSS determination requires 2-5 trials of constant load exercise, which limits the practical application in training. INSCYD software can calculate PMLSS (PMLSSINSCYD) based on physiological data that can be captured during a ~1h laboratory visit. To the best of our knowledge, the validity of the most recent software version has not yet been investigated. This study aimed to assess the validity of the software's calculations on PMLSS in cycling.The data for this study was retrieved from 2 published scientific sources (Weber, 2003;Kleinschmidt, 2004). Thirty-one cyclists (19 male, 12 female) performed a 15s sprint to estimate VLamax, a ramp test for 𝑉 ̇O2max assessment and 2-5 constant load tests to determine the PMLSS. INSCYD software was used to calculate PMLSS based on 𝑉 ̇O2max, VLamax, sex, body mass and body composition.PMLSSINSCYD was higher than PMLSS in the entire sample (mean difference: 4.6W, p<0.05, CI 95% 0.8-8.3W), in men (mean difference: 6.6W, p<0.05, CI 95% 1.3-11.8W), but not in women (mean difference: 0.8W, n.s., CI 95% -3.7 -5.3W) and within typical error of PMLSS estimations (~3%).In 12 subjects (9 male, 3 female) PMLSSINSCYD differed 3.1-7.3% compared to MLSS. Pearson correlations between the measured (PMLSS) and the calculated PMLSS (PMLSSINSCYD) were in men (r=0.974, p<0.001, CI 95% 0.933-0.99), women (r=0.984, p<0.001, CI 95% 0.931-0.996) and for the entire sample (r=0.992, p<0.001, CI 95% 0.982-0.996).It is concluded that the PMLSS can be accurately calculated with INSCYD software but still requires advanced testing equipment to collect valid 𝑉 ̇O2max and VLamax data.